Enhancing Knowledge and Awareness of Routine Hypertension Control and Medication in Panjang Jiwo, Surabaya - Kellyn Trycia Zenjaya; Ronald Pratama Adiwinoto; Callista Vivien Earlyanti; Bima Abdul Azis; Yahdiyan Fathir Fadhilah; Fairuziah Dinda Umardy; Amalia Dewindra Candra Puspita; Sekar Kurnia Cahya; Dinnara Nelya Rindayu; Vania Roanna Gabrielle (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Background: The Tenggilis Public Health Center (Puskesmas Tenggilis) is devoted to implementing Community Health Efforts (UKM) to ensure the provision of high-quality healthcare services, focusing on the measurement, monitoring, and supervision of local health problems. A Self-Assessment Survey (Survey Mawas Diri” (SMD) in Indonesian language) was conducted in Panjang Jiwo Village, Surabaya, revealing hyperten”sion as a primary health issue. Characterized by a systolic blood pressure ?140 mmHg and a diastolic pressure ?90 mmHg, hypertension remains widespread, with many residents unaware of the necessity for lifelong medication adherence and routine blood pressure monitoring. Methods: To address this health challenge, a thorough analysis was conducted, examining the root causes through the